Evaluation of the Influence of Social and Biological Factors on the Success of Exclusive Breastfeeding and Increased Baby Weight in Jakarta, West Java and Banten - Ita Herawati; Maiselamah; Rina Widiastuti; Rohmaulita Sinaga; Romarta Gabe Uli Kartika; Veronika; Wida Rosmala; Magfiroh (Jurnal Penelitian Pendidikan IPA, 2024)
Exclusive breastfeeding is crucial for the health and development of babies, reducing the risk of diseases such as respiratory infections, diarrhea, malnutrition, and even death. This study aims to evaluate the impact of social and biological factors on the success of exclusive breastfeeding and weight gain in babies in Jakarta and Banten. Using an analytical observational design with a case-control approach, 60 babies were involved (30 exclusively breastfed, 30 not). Chi-square analysis revealed significant influences on exclusive breastfeeding success from family knowledge (p=0.020), breastfeeding beliefs/culture in Jakarta (p=0.009), maternal nutrition (p=0.000), breastfeeding patterns (p=0.018), family support (p=0.000), and baby weight gain (p=0.000). However, beliefs/culture in Lebak Banten (p=0.429) and West Java (p=0.605) had no significant effect. These results highlight the importance of family support, proper maternal nutrition, and effective breastfeeding practices for exclusive breastfeeding success. Exclusive breastfeeding ensures optimal nutrition, boosts immunity, supports cognitive development, and lowers the risk of infant mortality and health complications.